The growth of buy-now-pay later : how it impacts on consumer financing and spending behavior - Cao Ba Thuy; Endress, Tobiass; Santoso, Djoen San; Junaid, Muhammad (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
No abstract
Special study submitted in partial fulfillment of the requirements for the Degree of Doctor of Business Administration
Keywords: Consumer credit; Consumer behavior; Consumption (Economics)